PENERAPAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN MINAT BELAJAR SISWA SMA KELAS X SMAN 8 BANDA ACEH - Yeti Hastuti; Yuli Amalia; Ahmad Nasriadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low interest of students in learning mathematics, especially in the material of Three Variable Linear Equation Systems (SPLTV), as well as the learning process that is still dominated by conventional methods so that students are less active in learning. This study aims to determine the effect of the application of the Realistic Mathematics Education (RME) approach to increasing the interest of class X students of SMAN 8 Banda Aceh. The research method used is quantitative research with a one group pretest-posttest design. The research subjects were 32 students of class X IPAS-3. Data collection techniques were carried out through pretest and posttest tests, learning interest questionnaires, and observations during the learning process. The results showed that the average pretest score of students was 45.63 while the average posttest score was 80.94, resulting in an increase of 35.31 points. The results after the questionnaire of student learning interest showed an increase with most students in the high and very high categories of learning application. In addition, the results of observations during three meetings showed an increase in student learning interest from 60% in the first meeting to 84% in the third meeting. The results of the paired t-test showed a significance value of 0.000 < 0.05 so that H₀ was rejected and H₁ was accepted. Thus, it can be concluded that the application of the Realistic Mathematics Education (RME) approach can increase students' interest in learning SPLTV material for class X IPAS-3 SMAN 8 Banda Aceh.